Application of the Reporting Entity Concept in Australia. (3rd December 2014) - Carey, Peter; Potter, Brad; Tanewski, George
<x xml:space="preserve">Abstract</x> For decades, the reporting entity concept has been the foundation of differential reporting in Australia. Those entities classified as 'reporting entities' are, prima facie, required to produce full GAAP‐based financial reports while other (non‐reporting) entities are generally able to produce less complex and shorter 'special purpose' financial reports. In recent years, the application of the concept, as originally set out in the Statement of Accounting Concepts (SAC) 1 Definition of the Reporting Entity, has been criticized on several grounds—particularly, that it does not yield the reporting outcomes originally intended by regulators. Our analysis of 1, 546 companies lodging financial statements with the corporate regulator in Australia (ASIC) shows the principles‐based criteria in SAC 1, designed to indicate the existence of a reporting entity, do not systematically explain its application by entities. Our findings are relevant for policy makers, researchers, and regulators concerned with how these choices might be more effectively regulated in future and whether this is best done through principles‐based or rules‐based approaches.